2017
DOI: 10.1038/ncomms14692
|View full text |Cite
|
Sign up to set email alerts
|

White matter maturation is associated with the emergence of Theory of Mind in early childhood

Abstract: The ability to attribute mental states to other individuals is crucial for human cognition. A milestone of this ability is reached around the age of 4, when children start understanding that others can have false beliefs about the world. The neural basis supporting this critical step is currently unknown. Here, we relate this behavioural change to the maturation of white matter structure in 3- and 4-year-old children. Tract-based spatial statistics and probabilistic tractography show that the developmental bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 65 publications
(97 reference statements)
8
81
1
2
Order By: Relevance
“…Most DMN studies show that the dorsal cingulum mediates the MPFC-PCC pathway, while the ventral cingulum supports communications between the PCC and ATL/AMG (Greicius, Supekar, Menon, & Dougherty, 2009;Sethi et al, 2015;van den Heuvel, Mandl, Kahn, & Hulshoff Pol, 2009;van den Heuvel et al, 2008). The TPJ connects with the ATL/AMG via the ILF (Horn, Ostwald, Reisert, & Blankenburg, 2014), and with the MPFC ventrally via the IFOF and dorsally via the SLF (Grosse Wiesmann et al, 2017;van den Heuvel et al, 2009). In the present study, we observed these reported structural connections and beyond that, we identified the whole connectivity profile of each social brain network, as well as the tract composition of each social pathway.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most DMN studies show that the dorsal cingulum mediates the MPFC-PCC pathway, while the ventral cingulum supports communications between the PCC and ATL/AMG (Greicius, Supekar, Menon, & Dougherty, 2009;Sethi et al, 2015;van den Heuvel, Mandl, Kahn, & Hulshoff Pol, 2009;van den Heuvel et al, 2008). The TPJ connects with the ATL/AMG via the ILF (Horn, Ostwald, Reisert, & Blankenburg, 2014), and with the MPFC ventrally via the IFOF and dorsally via the SLF (Grosse Wiesmann et al, 2017;van den Heuvel et al, 2009). In the present study, we observed these reported structural connections and beyond that, we identified the whole connectivity profile of each social brain network, as well as the tract composition of each social pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Benton tests, Philadelphia battery) (Gomez et al, 2015;Grossi et al, 2014;Thomas et al, 2008;Unger et al, 2016), and face memory tasks (e.g. Cambridge tests) (Gomez et al, 2015;Song et al, 2015;Unger et al, 2016); empathy was assessed by the "empathy quotient" (Chou et al, 2011;Herbet, Lafargue, Moritz-Gasser, Menjot de Champfleur, et al, 2015;Nakagawa et al, 2015;Takeuchi et al, 2013), the "interpersonal reactivity index" (Fujino et al, 2014;Parkinson & Wheatley, 2014), and the "trait emotional intelligence questionnaire" (empathy subsets) (Olszewski et al, 2017); mentalizing abilities were evaluated by "false belief" stories (Grosse Wiesmann et al, 2017), cartoon animations Scheibel et al, 2011), comic strip vignettes (Herbet et al, 2014;Kana et al, 2014), and the "reading the mind in the eyes" task (Anderson et al, 2015;Cabinio et al, 2015;Herbet et al, 2014;Mike et al, 2013;Yordanova et al, 2017). Such a wide variety of seemingly disparate disorders as well as diverse behavioral paradigms provide excellent opportunities for exploring the relationship between WM tracts and social functions.…”
Section: Methodological Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we find one of the most deleterious regulatory SNCs in the Netrin receptor UNC5D, which is critical for axon guidance(Takemoto et al 2011).We also detect changes in genes associated with myelination and synaptic vesicle endocytosis, critical to sustain a high rate of synaptic transmission, including DCX(Yap et al 2012), SCAP(Verheijen et al 2009), RB1CC1(Menzies et al 2015), ADSL(Jurecka et al 2012) and PACSIN1(Widagdo et al 2016) among others (Supplementary Information 2). It is noteworthy that among traits associated with cognitive functions such as language or theory of mind, the timing of myelination appears to be a good predictor of computational abilities(Skeide and Friederici 2016;Grosse Wiesmann et al 2017). Computational processing might have been facilitated by some of the changes presented here, at least in some of the circuits that have expanded in our lineage (Mars et al 2018), since subtle maturational differences early in development(Dubois et al 2016) may have had a considerable impact on the phenotype.…”
mentioning
confidence: 87%
“…All results were corrected for multiple comparisons. The group comparison analysis was corrected with thresholdfree cluster enhancement (TFCE) (Smith and Nichols 2009), and the brain-behavior correlations were corrected with a cluster-size correction using AFNI's (version 17.0.04) 3dFWHMx and 3dClustSim which has previously been used to relate behavior to FA and other tensor-derived indices (Grosse Wiesmann et al 2017;Neef et al 2018). The cluster-forming threshold was p < 0.01, and cluster size was significantly larger than needed for the p < 0.05 level.…”
Section: Discussionmentioning
confidence: 99%